2018
DOI: 10.1097/qad.0000000000001734
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Tat protein affects human CD4+ T-cell programing and activation, and favors the differentiation of naïve CD4+ T cells

Abstract: Tat affects the programing and functionality of CD4 T lymphocytes favoring the differentiation of naïve CD4 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
(67 reference statements)
1
17
0
Order By: Relevance
“…Earlier studies proposed that CD57 expression marked terminally differentiated Tmem that underwent activation-induced apoptosis in response to TCR stimulation (7,27), and our results confirm the findings that TCR engagement results in the death of these cells. However, we showed here that terminally differentiated CX3CR1 + CD57 + CD28 -CD8 + Tmem were capable of prolonged survival (via Bcl-2) and proliferation (via mTORC1) in response to IL-15.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Earlier studies proposed that CD57 expression marked terminally differentiated Tmem that underwent activation-induced apoptosis in response to TCR stimulation (7,27), and our results confirm the findings that TCR engagement results in the death of these cells. However, we showed here that terminally differentiated CX3CR1 + CD57 + CD28 -CD8 + Tmem were capable of prolonged survival (via Bcl-2) and proliferation (via mTORC1) in response to IL-15.…”
Section: Discussionsupporting
confidence: 91%
“…CD57 expression has been proposed to mark T cells near the end of their replicative capacity (7,27). Indeed, we found that sorted CX3CR1 + CD57 + CD28 -CD8 + Tmem had decreased viability after 7 days of TCR stimulation (Figure 4, A and B).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Briefly, whole blood was centrifuged at 2500 rpm (Megafuge 1.0R, Heraeus) for 7 min. to collect plasma, whereas the cellular fraction was loaded on Ficoll density gradient (GE Healthcare) to purify PBMCs, as previously described [29,30]. Plasma was stored at −20 • C and purified PBMCs were suspended in 90% foetal bovine serum (FBS) (Lonza) and 10% DMSO (Sigma-Aldrich) and then preserved in liquid nitrogen until use.…”
Section: Samples Purificationmentioning
confidence: 99%
“…time points after administration of Tat ( Figure 2 A). Previously, we have reported that Tat favors the late differentiation of T cells [ 38 , 40 , 52 ]. In addition, it has been shown that differentiated (e.g., effector memory) T cells are important correlates of protection in HSV-1 infection [ 16 , 17 , 18 , 19 , 53 ].…”
Section: Resultsmentioning
confidence: 99%